Sistem Pakar Diagnosa Penyakit Tanaman Rambutan dengan Metode Forward Chaining dan Certainty Factor Berbasis Android - Bayu Abrianto Risnadi; Fauziah Fauziah; Ratih Titi Komala Sari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The purpose of this research is to create an expert system application to diagnose diseases in the rambutan plant that can be accessed anytime and anywhere so that the handling of the disease can be done appropriately. The Forward Chaining and Definity Factor methods are used because they are very suitable for expert systems that diagnose something that is uncertain so that the manual calculation results from the symptom data and the existing expert values result in a 98.91% confidence level percentage, and solutions are given to treat disease-stricken plants. The implementation uses Android Studio so that the application can run dynamically on various devices so that farmers can immediately find out what is happening with the conditions of their rambutan plants directly.